LAYANAN KONSELING INDIVIDU DENGAN MEDIA KARTU BICARA DALAM MENGATASI SPEECH DELAY ANAK - Nisa, Khoirun; Suryati, Suryati; Bela Janare Putra (Counseling Milenial (CM), 2025)
Speech Delay is condition where a child experiences a delay in speech and language development compared to children his age. The purpose of this research is to find out the effectiveness of individual counseling services on “N” clients with speech card media in overcoming speech delay. This type of research is descriptive quantitative with a research population of 20 children aged 6 years. Purposive sampling technique with 1 speech delay child. Data collection tools using questionnaires, interviews, observations and documentation developed based on theory. Data analysis result using data normality test and paired sample T-Test in the experimental group before being given the Mean (SD) Treatment = 64,90 after being given the Mean treatment (SD) = 71,15 and in control group before being given the Mean (SD) treatment = 61,40 and Mean (SD) = 72,20 after being treated. The results show that individual counseling services with talking card media are effective in overcoming Speech Delay in Children.